Crimson phoenix : a Victoria Emerson thriller - Gilstrap, John (Pinnacle Books/Kensington Publishing Corporation, 2021)
John Gilstrap's post-apocalyptic new series featuring Victoria Emerson, a West Virginia congresswoman and single mother who becomes the last hope of a nation brought to the brink of destruction. The nightmare scenario has come to pass. America has fallen. In the aftermath, one woman becomes the last hope of a nation and its people in John Gilstrap's electrifying new Victoria Emerson thriller series. West Virginia Congresswoman Victoria Emerson has always put the needs of her community before the power games of Washington, D.C. Then an Army officer appears on her doorstep, deploying the code words "Crimson Phoenix"-meaning this is not a drill . The United States is on the brink of nuclear disaster. The major will escort her to a secure bunker. She cannot bring her family. A single mother, Victoria refuses to abandon her teenage sons. Denied entry to the bunker, the family somehow survives the unthinkable. In the aftermath, the nation is in chaos. The grid is gone. Food is scarce. Civility gives way to desperate survival. Against this total collapse, Victoria creates a new home in a small Appalachian mountain town. The community she builds around her shines like a beacon in a dark wasteland. Now she must defend it with her life-to give hope to a new America.